(untitled) (Mongolian Journal of Humanities and Social Sciences, 2025)
The interdisciplinary nature of modern linguistic research has led to the need to consider evaluation from the point of view of not only a linguistic phenomenon but also from the point of philosophy. As a philosophical category, evaluation was already expressed in the works of ancient thinkers and philosophers but still continues to be a source of interest and attention for scientific research. The opportunity to analyze the mentality and culture of nations is oral literature, proverbs, and legends. Even though there are fluent semantic analyses of proverbs, one of the least researched issues of proverbs is axiological aspects. There has been a growing need to evaluate proverbs on axiological method by a value theory. In the article titled “An axiological analysis of Mongolian proverbs with concepts of “goodness” in the framework of R.S. Hartman’s dimension,” some examples of Mongolian proverbs are studied according to the principles formulated by R.S. Hartman as the value form of “goodness” through systematically good, extrinsically good, and intrinsically good values. In doing so, the hermeneutics interpretation method, concept analyzing, and summarizing methods were used. According to the principle of Hartman’s identifying value of “goodness,” the characteristics of general features, plural meanings of cooperative meanings, and interdisciplinary studies were revealed in Mongolian proverbs. “Сайн” хэмээх ойлголт илэрхийлсэн монгол зүйр цэцэн үгсийг Гартманы акcеологийн онцлогийн үүднээс задлан шинжлэх нь Хураангуй: Улс үндэстний сэтгэлгээний онцлог, соёлыг судлах боломж, талбар бол тухайн ард түмний аман зохиол, зүйр цэцэн үгс, үлгэр домог юм. Зүйр цэцэн үгсийн утга зүйн судалгаа олон байдаг боловч үнэлэмжийн талаас судалсан судалгаа харьцангуй цөөн тул аксеологийг судлах тухайлсан төлөөлөгчийн байр суурин дээр үнэлэх хэрэгцээ шаардлага, үүсэж байна. Тус өгүүлэлд Монгол хэлний зарим зүйр цэцэн үгсийг Гартманы “сайн” үнэлэмжийн хэлбэр болох систематик, экстринсик, интринсик үнэлэмж гэж томьёолсон зарчмын дагуу судалсан болно. Ингэхдээ герменевтик тайлбарлахуйн арга, задлах, нэгтгэн дүгнэх аргыг ашиглав. Гартманы “сайн” үнэлэмжийн хэлбэрийг тодорхойлох зарчмын дагуу монгол хэлний зүйр цэцэн үгс дэх үнэлэмж, үүний дотор “сайн”-ы хэлбэрийг илрүүлэхэд монгол зүйр цэцэн үгс өргөн утгатай, нэг цогц зүйр үгс Гартманы үнэлэмжийн бүх хэлбэрээр тайлбарлагдах боломжтой гэж дүгнэхэд хүрэв. Түлхүүр үг: Зүйр цэцэн үгс, сайн, утга зүйн судалгаа, систематик үнэлэмж, экстринсик үнэлэмж, интринсик үнэлэмж